COVID-19 and the Vulnerabilities of Community-Dwelling Older Adults: Findings From a Statewide Survey of Home-Delivered Meals Recipients*. (8th March 2022) - Masters, Julie L.; Wilkinson, Lindsay R.; Kelly, Christopher M.; McKelvey, Miechelle; Ghazi Saidi, Ladan; Hill, Toni L.; Drozd, David; Wu, Heng; O'Brien, Taylor
COVID-19's impact on community-dwelling older adults, especially those in rural and underserved areas, as well as those who are homebound, is of interest to policy makers and clinicians, now and in the future. This study aims to examine the consequences of the COVID-19 pandemic on community-dwelling older adults with the greatest social and economic needs residing in a mostly rural state. Using a self-administered survey, we collected data from 1852 home-delivered meal recipients, age 60 years and older, served by Nebraska's eight Area Agencies on Aging. Results highlight three areas of importance: social connections, healthcare access and utilization, and technology. We found that while most older adults maintained social interaction, despite the restrictions imposed by the pandemic, feelings of loneliness persisted or even increased, with 35% of respondents feeling lonelier because of the pandemic. Our findings further reveal that 42% of older adults skipped or postponed healthcare visits during the pandemic, although the majority expressed interest in using telehealth. Finally, the rural‐urban divide was evident in our data, with less than one-half of respondents (45%) having access to reliable internet. Suggestions on how to prepare the most vulnerable people for similar crises are included.